2011
DOI: 10.1007/s00203-011-0735-4
|View full text |Cite
|
Sign up to set email alerts
|

Puf operon sequences and inferred structures of light-harvesting complexes of three closely related Chromatiaceae exhibiting different absorption characteristics

Abstract: Whole cells of the purple sulfur bacterium strain 970 exhibit an unusual absorption peak at 963 nm. Its closest relatives, Thiorhodovibrio (Trv.) winogradskyi DSM6702(T) and strain 06511 display a bacteriochlorophyll (BChl) a absorption peak at 867 nm that is characteristic for most light-harvesting complexes 1 (LHC1) of proteobacteria. The puf operons encoding the LHC1 and reaction center proteins were amplified, cloned, and sequenced, and for the Trv. winogradskyi, strains show the common pufBALMC gene arran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…9 ). These β-polypeptides correspond to the gene products of pufB 1 and pufB 2 reported previously 21 . All of the expressed LH1 polypeptides were assigned in the cryo-EM structure (Fig.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…9 ). These β-polypeptides correspond to the gene products of pufB 1 and pufB 2 reported previously 21 . All of the expressed LH1 polypeptides were assigned in the cryo-EM structure (Fig.…”
Section: Resultssupporting
confidence: 75%
“…strain 970 LH1 is that another histidine residue (His48) in the LH1 α-polypeptide, a residue absent from other purple bacterial LH1 α-polypeptides (Supplementary Fig. 8a ) 21 , also participates in hydrogen bonding with the C3-acetyl group of BChls a (Fig. 2c ) in addition to Trp47 that is conserved in all LH1 α-polypeptides.…”
Section: Resultsmentioning
confidence: 99%
“…The first is that the leucine typically found at position +12 in the LH1 α-polypeptide of other purple bacteria was replaced by a histidine (Figure S1); a model of this structure suggested that the His side chain was positioned near BChl a and could modulate its spectral properties. 21 The second concerns a deletion between α-Ser +6 and α-Asp +8 in the strain 970 LH1 α-polypeptide. However, Trv.…”
mentioning
confidence: 99%
“…tepidum LH1-RC complex revealed that this Ca 2+binding site is comprised of the side chain from α-Asp +13 , main chains from α-Trp +11 , α-Ile +16 , and β-Trp +9 , and two water molecules. 24 Because the LH1 αβ-polypeptides from strain 970 also contain these four amino acids, 21 we hypothesized that Ca 2+ could play a significant role in modulating the spectroscopic properties of the LH1-RC complex from this phototroph.…”
mentioning
confidence: 99%
“…castenholzii which unexpectedly has a type II RC complex, there is only one copy of puf A and puf B to produce the LH1 α‐/β‐apoproteins, respectively, and the RCs have high structural identity, but the number of LH1 α/β‐apoproteins range from 14 to 17. Meanwhile, some other bacteria possess multiple copies of the puf A and puf B genes , but their exact numbers and arrangement in the assembled LH1 is not clear. To address this question, the structures of the LH1‐RC super‐complexes from various species and with various numbers of puf A and puf B have to be solved.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%